A Review Article of Polyherbal Tablet for the Management of Osteoporosis - ., Pooja; Garg, Twinkle; Sharma, Ram Babu (Asian Journal of Pharmaceutical Research and Development, 2022)
Osteoporosis is an aging problem. The declining bone mineral density (BMD) enhances the chances of fractures during minor falls. Effective pharmaceuticals are available for a rapid improvement of BMD Osteoporosis is an enormous and growing public health problem. Once considered an inevitable consequence of ageing, it is now eminently preventable and treatable. Ironically, despite tremendous therapeutic advances, there is an increasing treatment gap for patients at high fracture risk. In this Series paper, we trace the evolution of drug therapy for osteoporosis, which began in the 1940s with the demonstration by Fuller Albright that treatment with oestrogen could reverse the negative calcium balance that developed in women after menopause or oophorectomy. We note a watershed in osteoporosis drug discovery around the year 2000, when the approach to developing novel therapeutics shifted from one driven by discoveries in animal studies and clinical observations (eg, oestrogen, calcitonin, and teriparatide) or opportunistic repurposing of existing compounds (eg, bisphosphonates) to one driven by advances in fundamental bone biology (eg, denosumab) coupled with clues from patients with rare bone diseases (eg, romosozumab, odanacatib). Despite these remarkable advances, concerns about rare side-effects of anti-resorptive drugs, particularly bisphosphonates, and the absence of clear evidence in support of their long-term efficacy is leading many patients who could benefit from drug therapy to not take these drugs. As such, there remains an important clinical need to develop ways to enhance patient acceptance and compliance with these effective drugs, and to continue to develop new drugs that do not cause these side-effects and have prolonged anabolic effects on bone. Such changes could lead to a true reversal of this potentially devastating disease of ageing.